Bilateral sparse transform for fast solving EM scattering problems by compressed sensing. Issue 14 (9th October 2017) - Cao, Xinyuan; Chen, Mingsheng; Wu, Xianliang; Kong, Meng; Qi, Qi; Zhang, Liang
Abstract : Rapid and accurate calculation of electromagnetic (EM) scattering problems over a wide incident angle range is always a difficult task which requires repeated numerical computation as the incident angle changes. Aiming at this subject, a solution that introduces compressed sensing into traditional method of moments is described, and the bilateral sparse transform method is first proposed to form a new scheme, in which the effectiveness is improved greatly since the total number of measurements required is reduced drastically as compared with the traditional unilateral sparse transform method. The basic principle is analysed in detail and the high effectiveness of bilateral sparse transform is verified by numerical results.